2014
DOI: 10.1007/s00239-014-9642-z
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Neutral Drift: Lessons From the In Vitro Evolution of Two Ribozymes

Abstract: The relative contributions of adaptive selection and neutral drift to observed genetic change are unknown, but likely depend on the inherent abundance of functional genotypes in sequence space and how accessible those genotypes are to one another. To better understand the relative roles of selection and drift in evolution, local fitness landscapes for two different RNA ligase ribozymes were examinedusing a continuous in vitro evolution system under conditions that foster the capacity for neutral drift to media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…Empirical studies of RNA-based fitness landscapes, biochemical model systems for the origin of life, also show that these landscapes consist of isolated fitness peaks with many non-viable genotypes [19,20]. The fact that both RNAbased landscapes [19,20] and these digital landscapes have similar structures suggests that the evolutionary patterns we see in these Avida experiments may be similar to those one would have seen in the origin of life on Earth. The presence of isolated genotype clusters in both digital and RNA fitness landscapes further suggests that the identity of the first self-replicator may determine life's future evolution, as other evolutionary trajectories are not accessible.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Empirical studies of RNA-based fitness landscapes, biochemical model systems for the origin of life, also show that these landscapes consist of isolated fitness peaks with many non-viable genotypes [19,20]. The fact that both RNAbased landscapes [19,20] and these digital landscapes have similar structures suggests that the evolutionary patterns we see in these Avida experiments may be similar to those one would have seen in the origin of life on Earth. The presence of isolated genotype clusters in both digital and RNA fitness landscapes further suggests that the identity of the first self-replicator may determine life's future evolution, as other evolutionary trajectories are not accessible.…”
Section: Discussionsupporting
confidence: 53%
“…While the fitness landscapes of some RNA-based genotypes have been mapped [19,20] (and other RNA replicators have been evolved experimentally [21]), in all such cases evolution already had the chance to shape the landscape for these organisms and "dictate", as it were, the sequences most conducive for evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In one example, selection for GTP aptamers directly yielded an optimal family of aptamer sequences, suggesting that these sequences were present in the initial pool; by contrast, other aptamer families improved their binding affinity by several orders of magnitude upon mutagenesis and re-selection, suggesting that the initial sequences of these aptamers were relatively far from optimal and required subsequent newly arising mutations for optimal activity 35,77 . To date, the evidence from NGS of in vitro selected pools suggest that individual families of functional RNAs exist in the starting pools, but greatly benefit from mutagenesis 15,46,77 or synthetic shuffling 45 to uncover the most active variants, which then do not tend to drift towards other peaks in the fitness landscape 78 .…”
Section: Types Of Mutations Recruitedmentioning
confidence: 99%
“…It is worth noting that these epistasic interactions are easily detected in this system because the distances between interacting sites in the linear nucleotide chain are typically shorter than sequencing read lengths, hence interaction sites can be collectively analyzed in single sequencing reads. It is important to appreciate that all evolutionary change occurring in the stem part of a ribozyme or an aptamer is epistatic in nature, thus epistasis is pervasive in this system 77,78,116 .…”
Section: Epistasismentioning
confidence: 99%
“…Nevertheless, the success of these selections suggests that there must be numerous functional families in the totality of sequence space [138,139]. More recently, extensive studies of the fitness landscapes of various functional RNAs have shown mostly isolated, sharp peaks with distinct structural motifs linked by generally unfavorable paths of mutation [140][141][142]. One recently proposed hypothesis is that molecular crowding and confinement may have played a role in increasing pathways of evolution [143], since crowding effects contribute to the folding stability of ribozymes [144][145][146][147][148] and reduce the effect of otherwise deleterious mutations [149].…”
Section: Current Biologymentioning
confidence: 99%